2008
DOI: 10.1089/vbz.2007.0123
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Amplification of West Nile Virus: The Role of Hatch-Year Birds

Abstract: Epizootic transmission of West Nile virus (WNV) often intensifies rapidly leading to increasing risk of human infection, but the processes underlying amplification remain poorly understood. We quantified epizootic WNV transmission in communities of mosquitoes and birds in the Chicago, Illinois (USA) region during 2005 and 2006. Using quantitative polymerase chain reaction (PCR) methods, we detected WNV in 227 of 1195 mosquito pools (19%) in 2005 and 205 of 1685 (12%) in 2006; nearly all were Culex pipiens. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
108
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 99 publications
(120 citation statements)
references
References 35 publications
11
108
0
1
Order By: Relevance
“…[2][3][4] Some general avian surveys reported that nestlings and immature birds were overrepresented in the virus-positive population, 5,6 and in one study peaks in West Nile virus (WNV) transmission were correlated with high seroprevalence and infection rates in hatching-year birds. 7 In contrast, other studies of WNV found relatively low seroprevalence in hatching-year birds in comparison to adults. 8,9 Nestling birds may be more susceptible to viruses and more negatively affected by them than are adults of the same species.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…[2][3][4] Some general avian surveys reported that nestlings and immature birds were overrepresented in the virus-positive population, 5,6 and in one study peaks in West Nile virus (WNV) transmission were correlated with high seroprevalence and infection rates in hatching-year birds. 7 In contrast, other studies of WNV found relatively low seroprevalence in hatching-year birds in comparison to adults. 8,9 Nestling birds may be more susceptible to viruses and more negatively affected by them than are adults of the same species.…”
Section: Introductionmentioning
confidence: 89%
“…16 Although some information on WNV pathology is known for relatively young individuals of several raptor species, 17,18 we know almost nothing about the clinical pathology of arboviruses in nestling passerine birds, 16 possibly because nestlings or recently fledged passerines are rarely found dead or exhibiting clinical pathology attributable to arboviruses. 6,7,19 One study reported WNV RNA in kidney tissue of field-collected blue jay ( Cyanocitta cristata ) nestling carcasses, but necropsy was not performed on these birds. 20 Understanding WNV disease etiology in nestling birds may assist in explaining patterns of virus or antibody prevalence in field surveys and yield insight into ways that the virus may be transmitted.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore sought to test the hypothesis that such negative virus-virus interactions might occur between CxFV and WNV in the field. We focused on an area of high WNV transmission in suburban Chicago, United States (Ruiz et al 2004), where our previous studies have demonstrated predictable seasonal WNV amplification in Culex mosquitoes coincident with annual peaks in human cases (Hamer et al 2008b). In particular, WNV transmission in this area is driven by Cx.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported differences in antibody prevalence between juveniles and adult birds. In many cases, adult bird antibody prevalence is higher than in juveniles (Gibbs et al 2006;Hamer et al 2008;Lampman et al 2013), which is explained by the additive effect of adult birds being exposed in prior years. However, few studies consider that antibody-negative adult birds could represent false negatives, due to waning antibodies, which could confound analyses that rely on antibody status to infer population metrics, such as mortality (Ward et al 2010;Kilpatrick et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Site descriptions and detailed sampling methods have been described for Chicago (Hamer et al 2008) and Atlanta (Levine et al 2013). Epitope blocked enzyme-linked immunosorbent assay (b-ELISA), as described by Hamer et al (2008), was used to detect WNV antibodies. Samples from all locations and times were tested in the same laboratory under the same conditions.…”
Section: Methodsmentioning
confidence: 99%